MRI of nasopharyngeal adenoid hypertrophy - Surov, Alexey (Neuroradiol J, 2016)
Nasopharyngeal adenoid hypertrophy (NAH) is a typical benign lesion. Due to involution, nasopharyngeal lymphatic tissue usually is not found in adults beyond the 30th to 40th year of life. However, occasionally NAH has been recognized after the 50th or 60th year. The aim of this study is to identify the frequency of NAH and to analyze its MRI findings in different age groups. From 2007 to 2011, 6693 MR investigations of the head were performed at our institution. MRI was obtained with a 1.5 T MRI device. NAH was identified in 18.0% of the patients. The frequency of NAH varied from 60.3% to 1.0% in the different age groups. The mean size of NAH was 23.2 ± 4.5 mm in cranio-caudal, 31.1 ± 5.2 mm in left-right, and 14.2 ± 4.1 mm in the anterior-posterior direction. The left-right and cranio-caudal sizes of NAH were largest in the 0–9 age group and decreased with age. On T1-w images most lesions (95.4%) were hypointense in comparison to the adjacent musculature. On T2-w fat-saturated images 82.4% of the lesions were hyperintense. After intravenous administration of contrast medium most lesions showed a slight enhancement (58.6%). Moderate enhancement was seen in 32.4% and a marked enhancement was identified in 9.0%. In the 0–9 age group most lesions showed a slight enhancement. Cysts within NAH were identified in 433 cases (35.9%). The frequency of cysts increased continuously with age, namely from 10.9% to 65.2%.